(untitled) (Research, Society and Development, 2025)
Introduction: Diabetic foot ulcers (DFUs) represent a serious complication of diabetes mellitus, associated with high morbidity and mortality and significant socioeconomic impact. Their increasing global prevalence poses challenges to health systems, requiring updated analyses of their clinical-epidemiological landscape. Objective: To systematically review the available evidence on the global burden of diabetic foot ulcers, emphasizing their prevalence, associated mortality, adverse clinical outcomes, and economic impact. Methods: A systematic review was conducted following PRISMA guidelines, registered in PROSPERO (CRD420251073475). Searches covered PubMed, SciELO, and LILACS (February–May 2025), including observational studies, clinical trials, and reviews published between 2020–2024. Results: Among the 10 studies analyzed, a high prevalence of DFUs was observed (ranging from 4% to 25% in people with diabetes), with concerning recurrence rates (up to 65% over 5 years). The most frequent complications included infections (30%–60% of cases), prolonged hospitalizations, and amputations (accounting for 80% of non-traumatic amputations). Direct costs were high, especially in cases requiring advanced therapies (tissue bioengineering, negative pressure therapy). Despite therapeutic advances (such as growth factors and artificial intelligence for prognosis), economic and operational barriers limit their widespread use. Conclusion: DFUs constitute a relevant public health problem, requiring integrated multidisciplinary approaches. Primary prevention strategies, early diagnosis, and policies ensuring equitable access to innovative treatments are urgently needed to reduce their global burden.